I have come across this question that I need a tip for.

Find the equation (general form) of the plane passing through the point $P(3,1,6)$ that is orthogonal to the vector $v=(1,7,-2)$.

I would be able to do this if it said "parallel to the vector"

I would set the equation up as $(x,y,x) = (3,1,6) + t(1,7,-2)$ and go from there.

I don't get where I can get an orthogonal vector. Normally when I am finding an orthogonal vector I have two other vectors and do the cross product to find it.

I am thinking somehow I have to get three points on the plane, but I'm not sure how to go about doing that.

Any pointers?

thanks in advance.

  • 3
    $(x,y,x) = (3,1,6) + t(1,7,-2)$ is not a plane, it is a line.... – N. S. Nov 14 '11 at 22:07
up vote 6 down vote accepted

For a plane in $\mathbb{R}^3$ with $\mathbf{r_0}$ a point that lies in the plane and $\mathbf{n}$ a vector normal to the plane, its equation can be given by: $$ \mathbf{n}\cdot(\mathbf{r}-\mathbf{r_0})=0 \quad \mbox{where} \quad \mathbf{r}=(x,y,z) $$

To solve your question, let us first rearrange the above equation: $$ \mathbf{n}\cdot(\mathbf{r}-\mathbf{r_0})=0 \quad\Rightarrow\quad \mathbf{n}\cdot\mathbf{r}-\mathbf{n}\cdot\mathbf{r_0}=0 \quad\Rightarrow\quad \mathbf{n}\cdot\mathbf{r}=\mathbf{n}\cdot\mathbf{r_0} $$

Substituting values, gives the following equation for the plane in Cartesian form: $$ (1,7,-2)\cdot(x,y,z) = (1,7,-2)\cdot(3,1,6) \quad \Rightarrow \quad x+7y-2z = -2 $$

  • @Cheesegraterr: If you would like more details, please let me know :) – matt Nov 27 '11 at 6:13
  • Does anything change if n is (or isn't) unit length? – David Doria Feb 11 '16 at 17:38

Key point:

A plane with normal vector $(n_1, n_2, n_3)$ has equation $$n_1 x + n_2 y + n_3 z = k$$ for some $k$.

Try solving $(P-r)\cdot v=0$, where $r =(x,y,z)$.

vector equation of a plane is in the form : r.n=a.n, in this case, a=(3,1,6), n=(1,7,-2). Therefore, r.(1,7,-2)=(3,1,6).(1,7,-2)
r.(1,7,-2)=(3x1)+(1x7)+(6x-2)

          r.(1,7,-2)=3+7-12
          r.(1,7,-2)=-2
   OR

r=(x,y,z)

therefore,

(x,y,z).(1,7,-2)=-2

      x+7y-2z=-2

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.